- #1

jesuslovesu

- 198

- 0

## Homework Statement

Well I've got another one that totally sucks.

[tex]y'' + 2y' + 5y = 4e^{-t}cos(2t)[/tex]

## Homework Equations

## The Attempt at a Solution

I tried Y(t) = [tex]Ae^{-t}cos(2t) + Be^{-t}sin(2t)[/tex] but that unfortunately yielded [tex]0 = 4e^{-t} cos(2t)[/tex]

So my question is how does one modify Y(t) in this type of situation? The only thing I can think of is something like [tex]Y(t) = Ae^{-t}t^2cos(2t) + Be^{-t}tsin(2t)[/tex] but that seems rather painful